The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10461-018-2280-5
|View full text |Cite
|
Sign up to set email alerts
|

Condomless Sex and Psychiatric Comorbidity in the Context of Constrained Survival Choices: A Longitudinal Study Among Homeless and Unstably Housed Women

Abstract: We sought to identify the prevalence and independent correlates of condomless sex within a cohort of community-recruited homeless and unstably-housed cisgender adult women who were followed biannually for three years (N=143 HIV+, N=139 HIV-). Nearly half (44%) of participants reported condomless sex in the 6 months before baseline, which increased to 65% throughout the study period. After adjusting for having a primary partner, longitudinal odds of condomless sex among women with HIV were significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…A Brazilian study showed that transgender women was eight and five times more likely to test positive for HIV and syphilis, respectively, than cisgender women and men [ 19 ]. The STIs can contribute to higher morbidity and mortality in the homeless population due the lack of care and access to health services [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian study showed that transgender women was eight and five times more likely to test positive for HIV and syphilis, respectively, than cisgender women and men [ 19 ]. The STIs can contribute to higher morbidity and mortality in the homeless population due the lack of care and access to health services [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The day-to-day challenges of having to prioritize access to government assistance over employment, and the ways in which housing instability destabilized engagement in HIV care were deeply rooted and intersecting themes observed across WLHIVs' HIV treatment challenges. Regarding efforts to end the HIV epidemic, previous work has observed that unsheltered WLHIV are less likely to receive and engage with HIV care (11,36,40,41) while simultaneously experiencing other risk factors that could impede efforts to reduce HIV transmission, like illicit drug use (37,42,43), risky sexual behavior (44)(45)(46), and poor mental health (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…In the U.S.-Mexico border region of San Diego, a focal point for "Ending the AIDS Epidemic," 2 and globally, HIV risk is higher among vulnerable cisgender women who experience violence, homelessness, and substance use. [3][4][5] In San Diego County, only 52% of cisgender women living with HIV (WLWH) were retained in HIV care and 62% were virally suppressed. 6 Latinos experienced as much as a 36% increase in HIV cases.…”
Section: Introductionmentioning
confidence: 99%